Feasibility study into the use of online instrumentation courses for medical radiation scientists. Issue 3 (August 2015) - MacDonald-Hill, J.L.; Warren-Forward, H.M.
Abstract A Medical Radiation Science (diagnostic radiography) instrumentation course historically taught face-to-face was taught fully online. The purpose of this study was to assess differences in academic achievement as well as gather feedback on student experiences. An anonymous online survey relating to student engagement and directions for future course development was distributed to all students who completed the course. The results clearly supports online delivery as students appreciated the ability to pause and rewind (94%) course content and work at their own pace (88%) whilst maintaining almost identical course results (p = 0.96). Future improvements would see the inclusion of interactive on-line modules and the re-introduction of face–face tutorials, appealing to students' desire for more support and human contact (27%) therefore reflecting the flipped classroom approach.